Epigenetic plasticity cooperates with cell-cell interactions to direct pancreatic tumorigenesis - Burdziak, Cassandra; Alonso-Curbelo, Direna; Walle, Thomas; Reyes, José; Barriga, Francisco M.; Haviv, Doron; Xie, Yubin; Zhao, Zhen; Zhao, Chujun Julia; Chen, Hsuan-An; Chaudhary, Ojasvi; Masilionis, Ignas; et al. (Science, 2023)
The response to tumor-initiating inflammatory and genetic insults can vary among morphologically indistinguishable cells, suggesting as yet uncharacterized roles for epigenetic plasticity during early neoplasia. To investigate the origins and impact of such plasticity, we performed single-cell analyses on normal, inflamed, premalignant, and malignant tissues in autochthonous models of pancreatic cancer. We reproducibly identified heterogeneous cell states that are primed for diverse, late-emerging neoplastic fates and linked these to chromatin remodeling at cell-cell communication loci. Using an inference approach, we revealed signaling gene modules and tissue-level cross-talk, including a neoplasia-driving feedback loop between discrete epithelial and immune cell populations that was functionally validated in mice. Our results uncover a neoplasia-specific tissue-remodeling program that may be exploited for pancreatic cancer interception.
Veröffentlicht: 12. Mai 2023
Gesehen am 07.08.2023